Other oriented perfectionism in tennis coaching - Hollowell, J.; Buscombe, R.; Preston, A. (Coaching and Sport Science Review, 2019)
Other oriented perfectionism describes a pre-occupation with the expectation that others will achieve excessively high standards of performance. Projecting unrealistic expectations on to each other in a player-coach dyad may disrupt the working relationship and impact on the athlete`s experience within the sport. This study uses Interpretive Phenomenological Analysis to explore, from the coach`s viewpoint, the effects of other oriented perfectionism in tennis coaching. After conducting semi-structured interviews with high level coaches from the United Kingdom, two superordinate themes emerged. `Negative effects of coaches` other-oriented perfectionism` and `Redefining perfectionism`. The findings of this study assist in highlighting areas for possible intervention as well as identifying avenues for future research.